2022
DOI: 10.1002/jcla.24477
|View full text |Cite
|
Sign up to set email alerts
|

Cell division control 42 elevates during infliximab therapy, and its increment relates to treatment response in ulcerative colitis patients

Abstract: Background: Cell division control 42 (CDC42) regulates multiple processes of inflammation and/or immunity in autoimmune diseases and also relates to the treatment efficacy of biologic regimens clinically. This study aimed to explore the longitudinal change in CDC42 during infliximab (IFX) treatment and its correlation with IFX response in ulcerative colitis (UC) patients.Methods: Active UC patients (N = 48) who received IFX were recruited, and their CDC42 expressions in peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The anti-TNF antibody infliximab, for example, has been proven to be effective in the induction and maintenance of clinical remission in IBD patients [166][167][168][169]. Recently, a study found that Cdc42 is upregulated in patients with UC in response to infliximab [170], but the mechanism underlying this upregulation still requires further studies.…”
Section: Clinical Prospect Of Rho Gtpasesmentioning
confidence: 99%
“…The anti-TNF antibody infliximab, for example, has been proven to be effective in the induction and maintenance of clinical remission in IBD patients [166][167][168][169]. Recently, a study found that Cdc42 is upregulated in patients with UC in response to infliximab [170], but the mechanism underlying this upregulation still requires further studies.…”
Section: Clinical Prospect Of Rho Gtpasesmentioning
confidence: 99%